Big Data Health Care Innovations: Performance Dashboarding as a Process of Collective Sensemaking - Hilco J van Elten; Sandra Sülz; Erik M van Raaij; Rik Wehrens (JMIR Publications, 2022)
International Registered Report Identifier (IRRID)RR2-10.2196/16779